An empirical framework for comparing effectiveness of testing and property-based formal analysis. - Bradbury, Jeremy S. (Software engineering notes.)
Today, many formal analysis tools are not only used to provide certainty but are also used to debug software systems - a role that has traditional been reserved for testing tools. We are interested in exploring the complementary relationship as well as tradeoffs between testing and formal analysis with respect to debugging and more specifically bug detection. In this paper we present an approach to the assessment of testing and formal analysis tools using metrics to measure the quantity and efficiency of each technique at finding bugs. We also present an assessment framework that has been constructed to allow for symmetrical comparison and evaluation of tests versus properties. We are currently beginning to conduct experiments and this paper presents a discussion of possible outcomes of our proposed empirical study.